Chained to the desk in a hybrid world : a guide to work-life balance - Robinson, Bryan E. (Tantor Media, Inc., 2023)
Americans love a hard worker. The employee who toils eighteen-hour days and eats meals on the run between appointments is usually viewed with a combination of respect and awe. But for many, this lifestyle leads to family problems, a decline in work productivity, and, ultimately, physical and mental burnout. Chained to the Desk in a Hybrid World provides an inside look at the impact of work stress on those who live and work with workaholics-partners, spouses, children, and colleagues-as well as the appropriate techniques for clinicians who treat them. This book builds on the research included in three previous editions of Chained to the Desk from the bestselling author and family therapist Bryan E. Robinson. In the wake of the COVID-19 pandemic and the rise of working from home, Robinson finds that the agonies of work stress have become more challenging. Recent years have seen an unprecedented shift to remote work, which has made it significantly harder to maintain the delicate work-life balance, weakened by smartphones and other technology. The result is that many workaholics are more stressed and burnt out than ever before in their work, despite being in the presence of family. Chained to the Desk in a Hybrid World both counsels and consoles. It provides a step-by-step guide to help listeners spot, understand, and ultimately recover from workaholism.